2012
DOI: 10.1016/j.canlet.2011.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of the PTPRO gene in peripheral blood as a potential biomarker in esophageal squamous cell carcinoma patients

Abstract: Inactivation of protein tyrosine phosphatase receptor-type O (PTPRO), a new member of the PTP family, by hypermethylation has been described in several forms of cancers. We evaluated PTPRO hypermethylation as a potential epigenetic biomarker in esophageal squamous cell carcinoma (ESCC). PTPRO hypermethylation was observed in 27 (75%) of 36 primary tumors and correlated significantly with depth of invasion (T-stage, P = 0.013). Among matched peripheral blood samples from ESCC patients, 13 (36.1%) of 36 had dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 27 publications
(25 reference statements)
3
33
0
Order By: Relevance
“…PTPRO promoter hyper methylation associated with a poorer survival rate for breast cancer The tumor suppressor properties of PTPRO gene have been evaluated across various cancer types such as esophageal carcinoma [40] and breast cancer [41]. A study by Li et al [42] included 98 primary breast tumor samples (not included in the TCGA database) from Shenzhen Maternal and Child Health Hospital showed that PTPRO promoter hyper methylation is associated with poorer overall survival (HR = 2.7; 95% CI: 1.1-6.2; p = 0.023).…”
Section: Case Studiesmentioning
confidence: 99%
“…PTPRO promoter hyper methylation associated with a poorer survival rate for breast cancer The tumor suppressor properties of PTPRO gene have been evaluated across various cancer types such as esophageal carcinoma [40] and breast cancer [41]. A study by Li et al [42] included 98 primary breast tumor samples (not included in the TCGA database) from Shenzhen Maternal and Child Health Hospital showed that PTPRO promoter hyper methylation is associated with poorer overall survival (HR = 2.7; 95% CI: 1.1-6.2; p = 0.023).…”
Section: Case Studiesmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36] The prognosis of ESCC remains to be poor with 5-year survival rate <20%. [37][38][39][40][41] In this study, we found that NCOA1 is highly enriched in human ESCC, and the levels of NCOA1 are clinically important in ESCC progression and patient prognosis. Functional studies demonstrated that NCOA1 is capable of promoting ESCC cell growth and progression.…”
Section: Introductionmentioning
confidence: 65%
“…Esophageal squamous cell carcinoma (ESCC) is the third most common malignancy of the digestive tract and the fifth leading cause of cancerā€related death worldwide . The prognosis of ESCC remains to be poor with 5ā€year survival rate <20% . In this study, we found that NCOA1 is highly enriched in human ESCC, and the levels of NCOA1 are clinically important in ESCC progression and patient prognosis.…”
Section: Introductionmentioning
confidence: 86%
“…For example, hepatocytes contain the full-length PTPRO protein, whereas it appears as a truncated form (PTPROt) in T cells, which are some of the main infiltrating inflammatory cells during FH. Most studies of PTPRO's role focused on cancer research; a common goal has been to define PTPRO as a tumor suppressor candidate (5)(6)(7)(8). Very recently, we (5) reported that PTPRO inhibits development of hepatocellular carcinoma by suppression of JAK2/STAT3 signaling; however, its role in liver inflammation is largely unknown.…”
mentioning
confidence: 99%